2010
DOI: 10.1177/0146167210385920
|View full text |Cite
|
Sign up to set email alerts
|

Moral Credentialing by Association: The Importance of Choice and Relationship Closeness

Abstract: People express more prejudice if they have established their "moral credentials." Five studies explored the acquisition of moral credentials through associations with racial minorities, particularly close relationships that are personally chosen. Participants choosing to write about a positive experience with a Black person (Study 1) or Hispanic person (Study 2) subsequently expressed more preference for Whites and tolerance of prejudice than did other participants. In Study 3, the credentialing effect of choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…First, Bradley-Geist et al (2010) predicted that participants who freely chose to write about a positive (vs. negative) experience with a member of a minority group would obtain a moral license, whereas participants who were forced to write about a positive (vs. negative) past experience with a member of a minority group would not obtain a moral license. Because in many other studies on moral licensing participants are specifically asked to write about moral behavior or moral traits in the past and thus do not have a choice to write about immoral versus moral behavior (Blanken, Van de Ven, & Zeelenberg, 2012;Blanken et al, 2014;Clot et al, 2013a;Conway & Peetz, 2012;Cornelissen, Bashshur, et al, 2013;Jordan et al, 2011;Sachdeva et al, 2009;Schüler, Lehnhardt, & Huber, 2012;Thomas & Showers, 2012;Young, Chakroff, & Tom, 2012), we decided to include the forced choice conditions from Bradley-Geist et al (2010). Second, in the Study 3 of Conway and Peetz (2012), the authors predicted that participants who wrote about moral actions would obtain a moral license, whereas participants who wrote about moral traits would not obtain a moral license.…”
Section: Moderatorsmentioning
confidence: 99%
“…First, Bradley-Geist et al (2010) predicted that participants who freely chose to write about a positive (vs. negative) experience with a member of a minority group would obtain a moral license, whereas participants who were forced to write about a positive (vs. negative) past experience with a member of a minority group would not obtain a moral license. Because in many other studies on moral licensing participants are specifically asked to write about moral behavior or moral traits in the past and thus do not have a choice to write about immoral versus moral behavior (Blanken, Van de Ven, & Zeelenberg, 2012;Blanken et al, 2014;Clot et al, 2013a;Conway & Peetz, 2012;Cornelissen, Bashshur, et al, 2013;Jordan et al, 2011;Sachdeva et al, 2009;Schüler, Lehnhardt, & Huber, 2012;Thomas & Showers, 2012;Young, Chakroff, & Tom, 2012), we decided to include the forced choice conditions from Bradley-Geist et al (2010). Second, in the Study 3 of Conway and Peetz (2012), the authors predicted that participants who wrote about moral actions would obtain a moral license, whereas participants who wrote about moral traits would not obtain a moral license.…”
Section: Moderatorsmentioning
confidence: 99%
“…Whereas prior research demonstrates how doing good can license people to act in morally dubious ways (for reviews, see Merritt, Effron, & Monin, 2010;Miller & Effron, 2010;Zhong, Liljenquist, & Cain, 2009), the present research suggests that merely reflecting on how one's prior behavior "could have been worse" is sufficient to provide a moral license. Moreover, in their strategic pursuit of such license (Bradley-Geist, King, Skorinko, Hebl, & McKenna, 2010;Merritt et al, 2012), people may distort their evaluations of the past to create the illusion that they passed up opportunities to transgress.…”
Section: Moral Behaviormentioning
confidence: 99%
“…Previous research shows that people feel less credentialed by minority acquaintances than minority friends (Bradley-Geist et al, 2010 Consistent with the DVs reported, more minority friends were associated with higher scores on all excluded DVs. In contrast with the DVs reported in Study 1, however, effects on these excluded DVs were not qualified by statement type.…”
Section: Limitations and Future Directionssupporting
confidence: 80%